Light Verbs in American and British Newspapers - Martín Sánchez, Beatriz (Journal of Artistic Creation and Literary Research, 2025)
This article deals with the use of light verbs in American and British newspapers and its characteristics and possible reasons for choosing them over lexical verbs. First, it examines the syntactic and semantic properties of light verbs. Secondly, it observes which type is more used in newspapers and the possible reasons for this. Finally, it compares the use of light verbs in The New York Times and The Guardian by analyzing ten articles from each newspaper. The results of the analysis highlight that make and take are the most utilized. Furthermore, make is the one that appears more frequently in both newspapers. The results suggest that the main reason for using light verbs is their capacity to modify the action.